Cartografia de Propaganda e Unidade Geográfica do Império (C. 1920-1945) - Costa, Nuno Silva (Africana Studia, 2020)
Starting from general aspects of the production of cartography of contemporary propaganda, we will try to understand how the colonial spaces were designed. That is, what kind of images, which forms and cartographic techniques were used in the internal construction of documents and how these tried to create and divulge certain representations of the ultramarine territories to the general public, considering the characteristics of the colonial imagery of the time, the transformations of the ideological visions and the colonial system itself.